eHealth services and technology: Challenges for co-development - Hyppönen, Hannele (Human Technology, 2007)
The promises of ICT have been poorly redeemed in health care; many projects have failed. This article conceptualizes the co-construction of services and technologies in order to help future practitioners in the field to understand and find solutions to the challenges in ICT-enhanced service change. The conceptualization is created by structuring the findings of a case study with the help of theoretical concepts. The conceptualization then is implemented in another case to study its potential for finding challenges and suggesting solutions. Both cases demonstrate challenges for codevelopment that contributed to poor project outcomes. Participants in eHealth projects need a better understanding of development as the parallel shaping of multiple objects. They need better skills in managing the change process and a better understanding of methods for collaboration throughout the development. The projects would benefit from networking with actors who have adequate understanding of the process as a whole and of methods of codevelopment.